Cell surface GRP78 regulates TGFβ1-mediated profibrotic responses via TSP1 in diabetic kidney disease - Trink, Jackie; Ahmed, Usman; O’Neil, Kian; Li, Renzhong; Gao, Bo; Krepinsky, Joan C. (Frontiers in Pharmacology, 2023)
Diabetic kidney disease (DKD) is the leading cause of kidney failure in North America, characterized by glomerular accumulation of extracellular matrix (ECM) proteins. High glucose (HG) induction of glomerular mesangial cell (MC) profibrotic responses plays a central role in its pathogenesis. We previously showed that the endoplasmic reticulum resident GRP78 translocates to the cell surface in response to HG, where it mediates Akt activation and downstream profibrotic responses in MC. Transforming growth factor β1 (TGFβ1) is recognized as a central mediator of HG-induced profibrotic responses, but whether its activation is regulated by cell surface GRP78 (csGRP78) is unknown. TGFβ1 is stored in the ECM in a latent form, requiring release for biological activity. The matrix glycoprotein thrombospondin 1 (TSP1), known to be increased in DKD and by HG in MC, is an important factor in TGFβ1 activation. Here we determined whether csGRP78 regulates TSP1 expression and thereby TGFβ1 activation by HG in primary MC. TSP1 transcript and promoter activity were increased by HG, as were cellular and ECM TSP1, and these required PI3K/Akt activity. To determine whether csGRP78 was required, its activity was inhibited using vaspin or the C-terminal targeting antibody C38. Alternatively, GRP78 translocation to the cell surface was prevented with siRNA downregulation of its transport co-chaperone MTJ-1. All prevented HG-induced TSP1 upregulation and deposition into the ECM. The HG-induced increase in active TGFβ1 in the medium was also inhibited, which was associated with reduced intracellular Smad3 activation and signaling. These data support an important role for csGRP78 in regulating HG-induced TSP1 transcriptional induction via PI3K/Akt signaling. Functionally, this enables TGFβ1 activation in response to HG, with consequent increase in ECM proteins. Means of inhibiting csGRP78 signaling represent a novel approach to preventing fibrosis in DKD.